OP0036 A phase 3 randomised, placebo-controlled, double-blind study of upadacitinib (ABT-494), a selective jak-1 inhibitor, in patients with active rheumatoid arthritis with inadequate response to conventional synthetic dmards. (12th June 2018) - Burmester, G.; Kremer, J.; van den Bosch, F.; Li, Y.; Zhou, Y.; Othman, A.; Pangan, A.; Camp, H.
Abstract : Background: Upadacitinib (UPA) is an oral, selective JAK-1 inhibitor in development for the treatment of patients (pts) with moderate to severe rheumatoid arthritis (RA) and other immune-mediated diseases. Methods: This Phase 3 study in pts with inadequate response (IR) to csDMARDs included a double-blind placebo (PBO)-controlled period (Period 1, reported here), during which pts were randomised 1:1:1 to receive once-daily (QD) extended-release formulation of UPA at 15 mg or 30 mg, or PBO for 12 weeks (wks). The primary efficacy endpoints were the proportion of pts who achieved an ACR20 response and the proportion who achieved DAS28-CRP low disease activity (LDA, ≤3.2) at Wk 12, using non-responder imputation (NRI). Results: Of 661 pts who were randomised, all received study drug, and 618 (93.5%) completed Period 1. At baseline, demographics and disease characteristics were similar across arms. The study met all primary and key secondary endpoints with p values<0.001 for both doses. At Wk 12, significantly more pts receiving UPA 15 mg and 30 mg QD vs PBO achieved an ACR20 response (63.8% and 66.2% vs 35.7%, p<0.001), and DAS28-CRP LDA (48.4% and 47.9% vs 17.2%, p<0.001) (table 1). Onset of action was rapid with significantly more pts in both UPA arms achieving ACR20 at Wk 1 vs PBO. At Wk 12, significantly more pts met ACR50 and ACR70 in the UPA 15 mg (38% and 20.8%) and 30 mg QD arms (43.4% and 26.5%) vs PBO (14.9% and 5.9%). Significantly more patients receiving UPA 15 mg and 30 mg QD vs PBO achieved DAS28-CRP<2.6 (30.8% and 28.3% vs 10%, p<0.001)] and CDAI-LDA (40.3% and 42% vs 19%, p<0.001), and pts receiving UPA at both doses experienced significantly greater improvements in DAS28-CRP, HAQ-DI, morning stiffness and FACIT-F vs PBO (p<0.001). Adverse events (AEs) and serious AEs were numerically higher with UPA than PBO (table 1). The overall incidence of infection was higher for UPA 15 mg and 30 mg QD vs PBO, but few were serious infections. There were 4 cases of herpes zoster/Varicella Zoster Virus infection (1 on PBO). Asymptomatic CPK elevations were only reported for patients on UPA. Two malignancies and 3 adjudicated cardiovascular events were reported. No PE/DVT were reported. There were no deaths, cases of TB or GI perforations. Types and frequency of laboratory abnormalities were similar to findings in Phase 2 studies with UPA. Conclusions: The efficacy of UPA at 15 mg and 30 mg QD vs PBO was demonstrated in this csDMARD-IR study population. The most notable responses were observed in the more stringent endpoints of LDA (by either DAS28-CRP or CDAI) and ACR70. The safety and tolerability profile was consistent with observations in the Phase 2 studies with UPA. Acknowledgements: AbbVie and the authors thank the patients, study sites and investigators who participated in this clinical trial. AbbVie, Inc was the study sponsor, contributed to study design, data collection, analysis and interpretation, and to writing, reviewing, and approval of final version. Medical writing support was provided by Naina Barretto, PhD, of AbbVie, Inc. Disclosure of Interest: G. Burmester Consultant for: AbbVie Inc., Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB., Speakers bureau: AbbVie Inc., Eli Lilly, Gilead, Janssen, Merck, Roche, Pfizer, and UCB., J. Kremer Shareholder of: Corona, Grant/research support from: AbbVie Inc, Consultant for: AbbVie Inc., BMS, Genentech, Gilead, GSK, Eli Lilly and Pfizer, Employee of: Corona, F. van den Bosch Consultant for: AbbVie Inc., Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer and UCB, Speakers bureau: AbbVie Inc., Celgene, Eli Lilly, Janssen, Merck, Novartis, Pfizer and UCB, Y. Li Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, Y. Zhou Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, A. Othman Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, A. Pangan Shareholder of: AbbVie Inc, Employee of: AbbVie Inc, H. Camp Shareholder of: AbbVie Inc, Employee of: AbbVie Inc,